Reversible Dilated Cardiomyopathy Due to Combination of Vitamin D–Deficient Rickets and Primary Hypomagnesemia in an 11-Month-Old Infant - Yazici, Mutlu Uysal; Kesici, Selman; Demirbilek, Hüseyin; Tanyıldız, Murat; Gumustas, Mehmet; Bayrakci, Benan (Journal of Pediatric Intensive Care, 2018)
Vitamin D–deficient rickets is still an important and common health problem in developing countries. Since calcium is an essential ion for cardiac muscle contraction, calcium deficiency caused by rickets can cause secondary dilated cardiomyopathy. This situation can be exacerbated by coexisting hypomagnesemia. Here, we report a case of dilated cardiomyopathy due to hypocalcemia induced by vitamin D–deficient rickets and accompanying primary hypomagnesemia in an infant whose cardiomyopathy was successfully treated by replacement of calcium, vitamin D, and magnesium. In addition to genetic causes, viral infections, and idiopathic factors, metabolic abnormalities are important etiologic factors in pathogenesis of dilated cardiomyopathy and since they are treatable, prompt diagnosis of these disorders is crucial.
Keywords: rickets; dilated cardiomyopathy; hypomagnesemia